2001
DOI: 10.1007/bf03217103
|View full text |Cite
|
Sign up to set email alerts
|

Identifying cognitive engagement in the mathematics classroom

Abstract: This paper reports an analysis of videotape and interview data from four Year 8 mathematics lessons from the perspective of student cognitive engagement. The study extends our understanding of cognitive engagement by locating empirical evidence for its occurrence within the classroom. On the basis of the data we have examined, it appears that cognitive engagement can be consistently recognised by specific linguistic and behavioural indicators and is promoted by particular aspects of the classroom situation, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
110
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 150 publications
(113 citation statements)
references
References 18 publications
2
110
0
1
Order By: Relevance
“…That is, these teacher behaviors were assumed to involve active student engagement. Furthermore, Helme and Clarke ( 2001 ) observed math classes for indicators of cognitive engagement such as self-monitoring, exchanging ideas, giving directions, and justifying answers. Finally, Lee and her colleagues used observational techniques to examine the quality of students' task engagement when involved in science activities (Lee & Anderson, 1993 ;Lee & Brophy, 1996 ) .…”
Section: Observationsmentioning
confidence: 97%
“…That is, these teacher behaviors were assumed to involve active student engagement. Furthermore, Helme and Clarke ( 2001 ) observed math classes for indicators of cognitive engagement such as self-monitoring, exchanging ideas, giving directions, and justifying answers. Finally, Lee and her colleagues used observational techniques to examine the quality of students' task engagement when involved in science activities (Lee & Anderson, 1993 ;Lee & Brophy, 1996 ) .…”
Section: Observationsmentioning
confidence: 97%
“…There were students discussing what they needed to do, planning, devising strategies, linking different parts of the work, looking up their notebooks to check for similar examples and checking the reasonableness of their results. (Extract 3) Helme and Clarke (2001) reported that cognitive engagement is more likely, when students work with peers on novel tasks that have personal meaning. As shown in the last column of Table 4, 54% of the articles coded high on novelty and that had any data on engagement included data where one or more forms of engagement could be ascribed to this dimension, most commonly this was behavioural engagement.…”
Section: Routine-novelmentioning
confidence: 97%
“…Drawing on the same theoretical rationale, this research has problematised both the explicit teaching of heuristics and those pedagogies that might be characterised as ''problem-based learning'' (Kirschner, Sweller, & Clark, 2006). Other Australian research aiming to provide teachers with information on choosing appropriate tasks has focused on the use of authentic artefacts or out-ofschool contexts (Lowrie, 2004(Lowrie, , 2005 as well as characteristics of tasks that increase cognitive engagement (Helme & Clarke, 2001;Williams, 2000). Clarke and Helme (1998) distinguished the social context in which tasks were undertaken from the ''figurative context'' described in the task itself and related this to the students' capacity to find points of connection between their own experience and what they are trying to understand or to solve.…”
Section: Teachers' Instructional Practicesmentioning
confidence: 97%